COVID-19 Pandemic and Bio-Ethical Challenges - Singh, Abhishek; Ohlan, Sunny; Agrawal, Deepika (Journal of Pharmacy Practice and Community Medicine)
The Coronavirus disease (COVID-19) wreaked havoc across the globe with the onset of year 2020, which posed an extra ordinary situation in front of humankind. As the pandemic continues to progress, everyday challenges are faced by health worker in the history of mankind, because medical profession is bound by ethics our health workers are facing unprecedented ethical dilemmas and challenges in the era of COVID-19 pandemic.